Functional 2D Iron‐Based Nanosheets for Synergistic Immunotherapy, Phototherapy, and Chemotherapy of Tumor. Issue 19 (12th August 2022) - Wang, Xingbo; Cheng, Yan; Han, Xiaoqing; Yan, Jiao; Wu, Yunyun; Song, Panpan; Wang, Yanjing; Li, Xi; Zhang, Haiyuan
Abstract: Immunotherapy efficacy has been limited by tumor‐associated macrophages (TAMs), which are the most abundant immune regulatory cells infiltrating around tumor tissues. The repolarization of pro‐tumor M2 TAMs to anti‐tumor M1 TAMs is a very promising immunotherapeutic strategy for cancer therapy. In this manuscript, multifunctional 2D iron‐based nanosheets (FeNSs) are synthesized via a simple hydrothermal method for the first time, which not only possess photothermal and photodynamic properties, but also can repolarize TAMs from M2 to M1. After modifying with polyethylene glycol and loading with bioreductive prodrug banoxantrone (AQ4N), abbreviated as AP FeNSs, it can effectively repolarize TAMs from M2 to M1 and deliver AQ4N to tumor microenvironment (TME). Moreover, the repolarized M1 TAMs overexpress inducible nitric oxide synthase, which can convert nontoxic AQ4N to cytotoxic AQ4 under hypoxic TME, enabling immunomodulation‐activated chemotherapy. A series of in vitro and in vivo results corroborate that AP FeNSs effectively exert photothermal and photodynamic effects and repolarize M2 TAMs to M1 TAMs, releasing inflammatory factors and activating the chemotherapeutic effect, thereby realizing synergistic tumor therapy. Abstract : 2D iron‐based nanosheets are designed to not only exhibit photothermal and photodynamic properties, but also to repolarize tumor‐associated macrophages (TAMs) from immunosuppressive M2 phenotype to immunostimulatory M1 phenotype, and nitric oxide synthase secreted by M1 TAMs can convert nontoxic AQ4N into toxic AQ4, thereby enabling immunomodulation‐regulated chemotherapy.